MODEL PEMBELAJARAN PENDIDIKAN PERDAMAIAN (KAJIAN AL-QUR’AN SURAT AL-NAHL) - Imam Sibaweh Al-Mawardi (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2019)
The learning model is a concept of planned success in all fields because the model is the necessary foundation or initial step that must have been arranged before implementing and determining to learn. Moreover, the model as an essential part that is inseparable from other components, especially the learning model applied in educational institutions, both formal, informal, and informal. So the purpose of the education model is in the learning process so that science is easily transferred and accessed and runs in an orderly, safe, controlled, and peaceful manner and produces useful knowledge. Peace education is an easy way to create a comfortable learning atmosphere and an effort to process students into superior and noble personalities, which refers to the source of Islamic teachings, namely the Qur'an because this is very important to be used as an educational reference. If you witness the latest phenomenon, it is found on social media and others, namely the number of lecturers, teachers, religious or political figures, they often express hate speech, hoaxes, provoke the public to be embedded in hatred, desolation and slander, even though they should giving enlightenment that makes the heart feel peaceful and comfortable and provides knowledge that is easily practiced and they should be used as role models. Among students are also frequent incidents of brawls, adultery, narcotics and traits that are not commendable, all of which are a big problem faced by this nation and must be quickly reacted and sought solutions, so as not to tradition and develop even greater, also the existence of conflict and life inconvenience. The presence of a peace education model as a breakthrough and a way out, because peace, comfort and prosperity and prosperity are noble ideals for every human being, for that if aspirations are to be carried out successfully, peace education should be taught to students from an early age. Therefore, education that breathes Islam is the answer and contribution from problems experienced by the nation, especially Muslims. Then the Al-Nahl Al-Qur'an outlines in detail and convincingly about the peace education learning model because in it contains many models, strategies and learning methods, including, hikmah, mauidzah hasanah, and mujadalah billati hiya ahsan